2022
DOI: 10.1016/j.xphs.2022.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Kinetics Of Liposomal Formulations of Differing Charge Influences Development of in Vivo Dendritic Cell Immunotherapy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Anionic formulations, such as DSPG, were previously described as tolerogenic toward DCs [32, 33]. However, in our recent study, treatment of DCs with empty liposome formulations, including DSPG(−), did not yield significant modulation of DC function, for example, IL‐10 production or maturation marker expression [25]. In contrast, here we show that upon differentiation with empty DSPG(−) liposomes, CD103 expression was significantly increased on DCs, to a similar degree as by soluble RA.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Anionic formulations, such as DSPG, were previously described as tolerogenic toward DCs [32, 33]. However, in our recent study, treatment of DCs with empty liposome formulations, including DSPG(−), did not yield significant modulation of DC function, for example, IL‐10 production or maturation marker expression [25]. In contrast, here we show that upon differentiation with empty DSPG(−) liposomes, CD103 expression was significantly increased on DCs, to a similar degree as by soluble RA.…”
Section: Discussionmentioning
confidence: 94%
“…For this study, we used anionic DSPG(−) liposomes loaded with RA since we previously showed that anionic formulations are more efficiently taken up by DCs than cationic liposomes [25]. Anionic formulations, such as DSPG, were previously described as tolerogenic toward DCs [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations